2017
DOI: 10.12911/22998993/70200
|View full text |Cite
|
Sign up to set email alerts
|

Varimax Model to Forecast the Emission of Carbon Dioxide From Energy Consumption in Rubber and Petroleum Industries Sectors in Thailand

Abstract: This study aims to analyze the forecasting of CO 2 emission from the energy consumption in the Rubber, Chemical and Petroleum Industries sectors in Thailand. The scope of research employed the input-output table of Thailand from the year 2000 to 2015.It was used to create the model of CO 2 emission, population, GDP growth and predict ten years and thirty years in advance. The model used was the VARIMAX Model which was divided into two models. The results show that from the first model by using which predicted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…Given that A 0 =B -1 Γ 0 , A 1 =B -1 Γ 1 and u t= B -1 ε t , then Equation ( 7) can be written as follows (Sutthichaimethee, 2017).…”
Section: The Varima -Ov I Model At Level 1: Varima -Ov (1)mentioning
confidence: 99%
“…Given that A 0 =B -1 Γ 0 , A 1 =B -1 Γ 1 and u t= B -1 ε t , then Equation ( 7) can be written as follows (Sutthichaimethee, 2017).…”
Section: The Varima -Ov I Model At Level 1: Varima -Ov (1)mentioning
confidence: 99%
“…In considering parameter γ t it is found that the increasing information of T will increase parameter value of γ t too. In case of time series X t at 2 time interval have correlation (or γ t 0) time series X t is memory of the process [60].…”
Section: Stationarymentioning
confidence: 99%
“…There are 2 series of time series, which are Y t and Z t . They can be written in the VAR(p) model as shown below [105,106].…”
Section: Sem-varimax Modelmentioning
confidence: 99%